2009
DOI: 10.1134/s1063773709110036
|View full text |Cite
|
Sign up to set email alerts
|

Stellar population of the irregular galaxy IC 10

Abstract: Based on our observations with the 6-m BTA telescope at the Special Astrophysical Observatory, the Russian Academy of Sciences, and archival Hubble Space Telescope images, we have performed stellar photometry for several regions of the irregular galaxy IC 10, a member of the Local Group. Distance moduli with a median value of (m − M) = 24.47, D = 780 ± 40 kpc, hav e been obtained by the TRGB method for several regions of IC 10. We have revealed 57 star clusters with various masses and ages within the fields us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…They detected several samples of old red giant stars (well fitted with isochrones of 13 Gyr) up to radial distances of 18–23 arcmin from the galactic centre, and an old star excess at least up to 34–42 arcmin from the centre. Similar results were also obtained by Tikhonov & Galazutdinova (), who detect an old stellar population coincident with the H i envelope. Thus, we can suppose that the external PNe are associated with the old and intermediate‐age stellar populations, since no young population is detected in the outskirts.…”
Section: Discussionsupporting
confidence: 90%
“…They detected several samples of old red giant stars (well fitted with isochrones of 13 Gyr) up to radial distances of 18–23 arcmin from the galactic centre, and an old star excess at least up to 34–42 arcmin from the centre. Similar results were also obtained by Tikhonov & Galazutdinova (), who detect an old stellar population coincident with the H i envelope. Thus, we can suppose that the external PNe are associated with the old and intermediate‐age stellar populations, since no young population is detected in the outskirts.…”
Section: Discussionsupporting
confidence: 90%
“…This means that the stellar halo and the hydrogen cloud have, within the errors, similar radial extents and resolve this peculiar feature of IC10 (Tikhonov & Galazutdinova 2009). Moreover, this evidence further supports the hypothesis that the hydrogen cloud is associated with the galaxy (stellar mass loss, pristine gas ;Huchtmeier 1979;Cohen 1979;Wilcots & Miller 1998).…”
Section: Resultsmentioning
confidence: 53%
“…Pointing δ includes 24 F 555W -band and 24 F 814W -band images of 500 s each. This pointing is located ∼3 NE of the galaxy center; it is outside the disk identified by Jarrett et al (2003; see the red ellipse in Figure 1) and inside the thick disk identified by Tikhonov & Galazutdinova (2009). The ground-based data were collected with the prime focus camera (Suprime-Cam, pointing ) on the Subaru telescope and with Mega-Cam on the Canada-France-Hawaii Telescope (CFHT, pointing ζ ).…”
Section: Photometric Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertain data due to inhomogeneous background in crowded stellar fields are given without error bars and are marked by a colon. In the first column, we also indicate the objects from the paper of Hunter (2001) (HX-X), and those which we consider to be common with the list of Tikhonov & Galazutdinova (2009…”
Section: A P P E N D I X a : P H Oto M E T Ry O F C L U S T E R S I Nmentioning
confidence: 99%